Chapter Clean Water from Clean Energy: Decentralised Drinking Water Production Using Wind Energy Powered Electrodialysis - Malek, Payam (InTechOpen, 2016)
Supply of potable water requires energy and unfortunately most of the countries with minimal access to safe drinking water are also poor in terms of access to reliable energy grids. However, many of such regions have access to other sources of water (such as brackish and groundwater) that can be treated for producing drinking water if correct treatment systems are put in place. Moreover, many of the electrically remote areas are rich in terms of renewable energy (RE) resources (such as wind and solar) which can be potentially employed as the main source of energy for powering water purification systems. Therefore, development and implementation of off‐grid RE powered contaminant removal systems, for producing freshwater from available resources (such as brackish and groundwater), can be considered as an effective and potentially sustainable solution for overcoming the drinking water scarcity issue in remote regions of developing countries. This chapter revises the state of the art related to desalination systems using electrodialysis technology powered by wind energy for decentralised water production.